Pengaruh Konsentrasi Ekstrak Etanol dari Daun Sembukan (Paederia foetida L) Sebagai Inhibitor Korosi Logam Besi padaLarutan HCl 1M dan Air Laut - Novitaningrum, Elis; Setiawan, Mohammad Arfi; Trisnawati, Ade (Eksergi, 2023)
The massive development of industry creates human using various of metal which available in the nature for being contruction, for example a Iron metal. The iron is a transition metal on periodic table which often used on industry and building construction, however iron is a corrodiable metal. The metal  corrotion must be solved cause create many of loss.  Therefore, the study aimed to examine sembukan leaf extract in various consentration, 0%, 2%, 4%, 6%, 8% to seawater and HCl 1M during 7 days of contact moment. The correlation strenght between variable using regression linier method. Based on study that  the higher consentration inhibitor and the corrotion rate decreases. He highest efficiency using seawater is 89,9% and using HCl 1 is 68,9%. The highest correlation between variable is 93,2% using seawater. Th e conclution  is sembukan leaf extract effective  to protect iron corrotion of seawater